THE RESULTS OF ACL RECONSTRUCTION WITH REPAIR OF POSTERIOR HORN OF THE MENISCUS - Minh Dương, Nguyễn; Thành Toàn, Võ; Hoàng Viễn, Ngô; Duy, Đỗ (Journal of Health and Aging, 2025)
To evaluate the results of ACL reconstruction with repair of posterior horn of the meniscus. prospective study of 34 patients with ACL rupture with posterior horn of the meniscus tear underwent elective knee arthroscopy at Thong Nhat hospital from March 2020 to March 2023. There are 17 males and 17 females. Mean age was 36 years (from 18 to 50 years). Body mass index (BMI): average 24 (range 18 to 32). Mechanism of injury: 42.3% sports accidents, 32.7% traffic accidents, 25% daily life accidents. The mean time before surgery was 44 days (4-180 days). Posterior horn medial meniscus tear accounts for 38.2% of patients and lateral horn medial meniscus tear accounts for 61.8% of patients. Chondral lesions according to Outerbrigde: 70% grade 2, 17% grade 1 and 13% grade 3. After 1 year, the mean IKDC score was 78.28 points (from 68 to 83 points), the mean Lysholm score was 88.28 points (from 70 to 94 points). Patients with knee joint stability after 1 year of follow-up have a rate of over 88.2%, patients with good symptoms of a meniscus tear after 1 year of follow-up have a rate of over 73.5%. All patients were satisfied. 83% of patients with grade I and 17% of patients with grade II according to K-L system for classification of osteoarthritis on X-ray of the knee joint after 1 year. No complications of infection, delay healing, nerve or vascular injuries, pulmonary embolism, deep vein thrombosis; 21.2% of patients had synovitis. ACL reconstruction with repair of posterior horn of the meniscus gave satisfactory results